The Ethics of Military Influence Operations - Skerker, Michael (Conatus - Journal of Philosophy, 2023)
This article articulates a framework for normatively assessing influence operations, undertaken by national security institutions. Section I categorizes the vast field of possible types of influence operations according to the communication’s content, its attribution, the rights of the target audience, the communication’s purpose, and its secondary effects. Section II populates these categories with historical examples and section III evaluates these cases with a moral framework. I argue that deceptive or manipulative communications directed at non-liable audiences are presumptively immoral and illegitimate for liberal states, as are deceptive operations aimed at an unjust end, or even operations aimed at a just end where secondary effects are forecast to be disproportionate to the proximate end.